The Determinants of Income Distribution, an Empirical Analysis of Developing Countries - Naz Ata, Farah; Alam, Shaista; Saeed, Noman (Public Finance Quarterly, 2019)
Income Distribution, which is a center of discussion in economic theory, has recently evolved from theory to application. The role of the government and institution in income distribution, especially in the developing countries, needs in-depth evaluation so that further policies can be constituted. This aspect of income distribution has often been empirically explored in developed countries but there is still gap present in developing countries. The present study is an attempt to fill the gap in research related to fiscal, institutional and macroeconomic determinants of income distribution in a sample of 50 developing countries through using Panel Estimation Technique covering a period from 1995 to 2015 with five years frequency. The study analyzes income distribution from three dimensions: Gini coefficient, Income share of the poorest 20% and Poverty gap. The study finds that while government current spending hinders equal distribution of income, social spending facilitates it. Control of corruption and improvement in bureaucratic quality has negative effects on the redistribution of income. Rising inflation appears to temporarily benefit the poorest income share while unemployment, per capita income and trade openness does the opposite.